2019
DOI: 10.1371/journal.pone.0220567
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Substrate-1 (IRS-1) and IRS-2 expression levels are associated with prognosis in non-small cell lung cancer (NSCLC)

Abstract: The insulin-like growth factor-1 (IGF-1) signaling pathway has been implicated in non-small cell lung cancer (NSCLC) outcomes and resistance to targeted therapies. However, little is known regarding the molecular mechanisms by which this pathway contributes to the biology of NSCLC. The insulin receptor substrate (IRS) proteins are cytoplasmic adaptor proteins that signal downstream of the IGF-1R and determine the functional outcomes of this signaling pathway. In this study, we assessed the expression patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Chronic hyperinsulinemia has been proposed to play a role in the growth of non-small-cell lung cancer, with data suggesting that chronic stimulation of the insulin-like growth factor-1 signaling pathway may promote the rapid growth of existing neoplasms [19,20]. This observation is supported by data demonstrating an overall increased risk of any malignancy in the population of patients with long-standing diabetes.…”
Section: Discussionmentioning
confidence: 90%
“…Chronic hyperinsulinemia has been proposed to play a role in the growth of non-small-cell lung cancer, with data suggesting that chronic stimulation of the insulin-like growth factor-1 signaling pathway may promote the rapid growth of existing neoplasms [19,20]. This observation is supported by data demonstrating an overall increased risk of any malignancy in the population of patients with long-standing diabetes.…”
Section: Discussionmentioning
confidence: 90%
“…IRS2, a cytoplasmic adaptor protein, mediates the effects of insulin as well as IGF1 and therefore plays a role in growth-promoting IGF1 receptor (IGF1R) signaling. Overexpression is associated with increased glucose metabolism and tumor invasion as well as decreased overall survival and disease progression in patients [ 97 , 98 ]. Therefore, the downregulation of IRS2 by hyperinsulinemia lowered tumor invasion and metastasis in the present study, which has also been proven in an obese and diabetic mouse model [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Han et al reported that 43.6% of NSCLC specimens showed loss of IRS-1 expression, and downregulation of IRS-1 is more frequently observed in squamous cell carcinoma than other type lung cancer [ 40 ]. Meanwhile, low IRS-1 cytoplasmic expression also showed a trend toward association with decreased overall survival in squamous cell carcinoma patients [ 41 ]. In this study, IRS-1 was relatively highly expressed in A549, H1299, and LTEP-a2 cells, which might be due to these NSCLC cells being adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%